Superoxide stimulates a proton leak in potato mitochondria that is related to the activity of uncoupling protein. - Considine, M; Goodman, M; Echtay, K; Laloi, M; Whelan, J; Brand, MD; Sweetlove, L (2003)
The ability of plant mitochondrial uncoupling proteins to catalyze a significant proton conductance in situ is controversial. We have re-examined conditions that lead to uncoupling of mitochondria isolated from the tubers of potato (Solanum tuberosum). Specifically, we have investigated the effect of superoxide. In the absence of superoxide, linoleic acid stimulated a proton leak in mitochondria respiring NADH that was insensitive to GTP. However, when exogenous superoxide was generated by the addition of xanthine and xanthine oxidase, there was an additional linoleic acid-stimulated proton leak that was specifically inhibited by GTP. Under these conditions of assay (NADH as a respiratory substrate, in the presence of linoleic acid and xanthine/xanthine oxidase) there was a higher rate of proton conductance in mitochondria from transgenic potato tubers overexpressing the StUCP gene than those from wild type. The increased proton leak in the transgenic mitochondria was completely abolished by the addition of GTP. This suggests that superoxide and linoleic acid stimulate a proton leak in potato mitochondria that is related to the activity of uncoupling protein. Furthermore, it demonstrates that changes in the amount of StUCP can alter the rate of proton conductance of potato mitochondria.